If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 84 = 12(X) Solving 84 = 12X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-12X' to each side of the equation. 84 + -12X = 12X + -12X Combine like terms: 12X + -12X = 0 84 + -12X = 0 Add '-84' to each side of the equation. 84 + -84 + -12X = 0 + -84 Combine like terms: 84 + -84 = 0 0 + -12X = 0 + -84 -12X = 0 + -84 Combine like terms: 0 + -84 = -84 -12X = -84 Divide each side by '-12'. X = 7 Simplifying X = 7
| 5x+2x^2+3x-4x^2= | | 7x-2*2=10 | | 5x+2x^3-9x-8x^3= | | -6(1+5l)=54 | | 4x^2+6x=y-2 | | 3p-5=(p-1)(p-2) | | (x+4)(x+4)-14=0 | | 7x/35=4x-5/6 | | 2x^2+85-10=0 | | 2x+2=35 | | 4a+(-7a)= | | 18=3(3e-6) | | x^2-500*x+1000=0 | | 1/5x5/6 | | x^3-7x^2+14x-3=0 | | 9y+2y-3y= | | z+9=y+12 | | -5(2t+7)=-15 | | 3(f-2)=3 | | 81x^2/441=0 | | 10(s-7)=-108 | | 72=16t^2+64t+12 | | 5(m+10)=80 | | 6(4s+8)=144 | | 3*x=15-y | | 7(2l+4)=154 | | 3x+99=11x-13 | | 6x-1=12x-59 | | 3(x-2)+2(x-3)=5x-12 | | a+b+c+d+e=1139 | | 2x^2-9y^2=0 | | 3y/2x=x/3y |